Cell primitive-based biomimetic nanomaterials for Alzheimer's disease targeting and therapy - Tong Yin; Yan Liu; Bin He; Baofeng Gong; Jianjian Chu; Chao Gao; Wendanqi Liang; Mengqi Hao; Wenjing Sun; Jianhua Zhuang; Jie Gao; You Yin (Materials Today Bio, 2023)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder, which is not just confined to the older population. Although developments have been made in AD treatment, various limitations remain to be addressed. These are partly contributed by biological hurdles, such as the blood–brain barrier and peripheral side effects, as well as by lack of carriers that can efficiently deliver the therapeutics to the brain while preserving their therapeutic efficacy. The increasing AD prevalence and the unavailability of effective treatments have encouraged researchers to develop improved, convenient, and affordable therapies. Functional materials based on primitive cells and nanotechnology are emerging as attractive therapeutics in AD treatment. Cell primitives possess distinct biological functions, including long-term circulation, lesion site targeting, and immune suppression. This review summarizes the challenges in the delivery of AD drugs and recent advances in cell primitive–based materials for AD treatment. Various cell primitives, such as cells, extracellular vesicles, and cell membranes, are presented together with their distinctive biological functions and construction strategies. Moreover, future research directions are discussed on the basis of foreseeable challenges and perspectives.